Sealed-cavity resonant microbeam pressure sensor - Burns, D.W.; Zook, J.D.; Horning, R.D.; Herb, W.R.; Guckel, H. (Sensors and actuators. A. Physical., 1995)
A quasi-digital pressure sensor based on polysilicon resonant microbeams has been demonstrated. Pressure sensitivities of nearly 4000 counts per second per psi have been attained on a 10 psi device with a base frequency of 233 000 Hz. Short-term stability as low as 0.01 ppm of the base frequency is typical. The microbeams are fabricated with their own integral vacuum cavities, allowing high- Q operation in the differential pressure mode or in contact with liquids such as silicone oil. Design considerations include the effects of internal strain and lead to a push-pull layout configuration independent of microbeam strain or diaphragm thickness. Fabrication technology incorporates fine-grained polysilicon, surface micromachining, bulk micromachining, and reactive sealing. Packaging into precision avionics headers is being used for preliminary testing. Testing results indicate suitability for precision avionics, industrial, and commercial applications. Optical methods have been used to test resonant microbeam pressure sensors and verify the push-pull design methodology. Testing methods developed under this effort include electrostatic drive/piezoresistive sensing, optical drive/optical sensing, substrate piezoelectric drive/optical sensing, and electrostatic drive/laser vibrometer sensing. Wafer-level testing of 200 μm×46 μm×1.9 μm microbeams shows an average fundamental frequency of 553 150 and first overtone of 1 332 550 Hz. The standard deviations across the wafer are 0.15 and 0.10%, respectively. The internal strain and effective thickness can be determined with high resolution. Laser vibrometer measurements through the microbeam shell verify the fundamental frequency and reveal at least ten overtones up to 25 MHz.